Rethinking the Digital Divide in relation to Visual Disability in India and the United States: Towards a Paradigm of ’Information Inequity’ - Chaudhry, Vandana; Shipp, Thomas (Disability Studies Quarterly, 2005)
This paper considers the barriers to information access faced by visually disabled people in the epoch of the information revolution. The authors question the inadequacy of the popular mechanistic-binary conception of the digital divide and propose a new paradigm "information inequity." This model aims toward a holistic conception of the realities of information access and marginalization for visually disabled people. The paper critiques the mechanistic-binary notion of a "digital divide" where one is either "info-rich" or "info-poor" based on the availability of technology. The paper adopts a cross-cultural perspective, considering digital disablement of visually disabled people in India and the United States. By considering the economic, political, cultural and educational aspects of marginalization, as well as the technological, the authors set out to delineate the relationship between disability, technology and society.